Unilever’s Customer Data Management Information System in Medan City and Approaches to Android Smartphone and IoT Flexibility - Purba, Windania (Internet of Things and Artificial Intelligence Journal, 2021)
A web application is a type of application that uses browser technology to run an application accessed via a mobile network. In this case, the web application can also assist in collecting customer data, especially those carried out by Unilever companies, where the system is quite efficient and accurate in collecting customer data. This system also makes it easier for companies engaged in data collection. In this case, the employees can easily record every customer and see the number of products used and selling well in the market. This is where the Unilever company will know how many products will continue to be produced and marketed. Furthermore. This paper discusses the development plan for this W.E.B. application towards Smartphone mode and development towards the Internet of Things for flexibility when accessing and getting data in real-time.